Islamic Educational Values in Qona’ah: A Literature Review from the Perspectives of Sufism and Character Education - Huda, Khusnul (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze and conceptualize the Islamic educational values embedded in the attitude of qona’ah (contentment) and to explore its relevance as a foundational principle for character education within contemporary Islamic educational contexts. Although Islamic education emphasizes moral and spiritual formation, many educational practices still prioritize cognitive achievement while neglecting the internalization of spiritual dispositions that shape ethical behavior and psychological resilience. This research therefore seeks to reposition qona’ah not merely as a personal virtue but as an operational educational value capable of strengthening holistic character development. Methodologically, the study employs a qualitative library research design using a descriptive-analytical approach. Data were collected from classical Islamic sources, Sufi ethical literature, and peer-reviewed scholarly publications on Islamic education and character development. The selected literature was systematically reviewed, categorized, and critically analyzed to identify conceptual patterns, theoretical relationships, and pedagogical implications of qona’ah within Islamic educational frameworks. The findings indicate that qona’ah plays a significant role in shaping students’ moral self-regulation, emotional stability, gratitude, and moderation in material pursuits. These dispositions contribute not only to spiritual maturity but also to psychological well-being and social responsibility. The study demonstrates that integrating qona’ah into educational practices through habituation, modeling, and value-based curricula can enhance character formation more effectively than behavior-oriented approaches alone. The novelty of this study lies in its synthesis of classical Islamic spirituality, Sufi ethics, and modern character education theory into a coherent conceptual framework that positions qona’ah as a teachable and measurable educational construct. This research contributes theoretically by enriching the discourse on Islamic educational values and practically by offering educators and policymakers a value-based model for developing morally grounded, resilient, and socially responsible learners.